Dysregulation of erbB family genes and ErbB (HER) receptors in pheochromocytoma - Babińska, Anna; Żaczek, Anna; Falkiewicz, Bogdan; P. Bielawski, Krzysztof; Sworczak, Krzysztof; Lisowska, Urszula (Contemporary Oncology/Współczesna Onkologia, 2004)
The paper reviews current knowledge on mutations and expression abnormalities of the ErbB (HER) family receptor tyrosine kinases in human pheochromocytoma . Genes of the erbB family encode four tyrosine kinases (ErbB-1 or EGFR, ErbB-2, ErbB-3, and ErbB-4), which are expressed on the surface of various cells, mainly from epidermal and mesenchymal tissues. Genes of the erbB family and products of their expression are involved in the growth and proliferation, apoptosis, protein secretion, differentiation and motility of cells, morphogenesis of organs and regeneration of diverse tissues, and they play a significant role in numerous carcinogenic processes. During the development of neoplasm they are frequently subject to gene amplification, point mutations and deletions, or gene expression alterations, probably leading to oncogenic activation. However, their role in the development of neuroendocrine tumors is relatively poorly known. Only a few studies on human pheochromocytoma have been published so far and their results are ambiguous. These studies found e.g. some correlations between ErbB receptors expression and the presence of a malignant or recurrent form of PHEO, but not all studies confirmed the observations. Mutations like erbB gene amplification or deletion are very frequent in pheochromocytoma ; in the study conducted in our laboratory their presence was detected using ddPCR in 69% of tumors tested. This can show that abnormalities within erbB oncogenes have a significant role in the development of PHEO. However, to prove it, a prospective observation of a large patients’ group is necessary.